Pokok-Pokok Pemikiran Sufi Imam Junaid Al-Baghdadi: Analisis Tasawuf Sunni Klasik - Akhmad Rofii Damyati; Nukman bin Jurkapali (STAI Al-Mujtama Pamekasan, 2024)
This article examines the core ideas of Junaid al-Baghdadi as a central figure in the formation of classical Sunni Sufism. The main focus of this study is an analysis of the concepts of tawḥīd, fanāʾ–baqāʾ, ṣaḥw (spiritual awareness), and the integration between sharīʿah and ḥaqīqah. The research employs a qualitative method based on literature study with a descriptive-analytical approach to both classical sources and contemporary academic studies. The results indicate that Junaid al-Baghdadi developed a moderate and systematic model of Sufism, emphasizing a balance between the exoteric dimension (sharīʿah) and the esoteric dimension (ḥaqīqah). He rejected extreme forms of Sufism that disregard sharīʿah norms and emphasized the importance of rational control in mystical experiences. His concept of ṣaḥw serves as the foundation for a “conscious” and measured Sufism, in contrast to the ecstatic (sukr) model that tends to be expressive. This article concludes that Junaid al-Baghdadi’s thought makes a fundamental contribution to constructing an integrative and ethical Sunni Sufi paradigm that remains relevant within the context of contemporary Islamic spirituality.